Coping through self-esteem - McFarland, Rhoda (New York : Rosen Pub. Group, 1988)
Offers advice on how to build self-esteem in order to deal with everyday problems and relationships in a positive and healthy manner.
Includes index.
Keywords: Self-esteem in adolescence -- Juvenile literature; Assertiveness in adolescence -- Juvenile literature; Self-esteem.; Assertiveness (Psychology)